Representation of Early Childhood Character Values in the Animated Film Jumbo at the Pocenter Playgroup - Nia Febrianti; Betty Yulia Wulansari; Nurtina Irsad Rusdiani (LPPM Institut Pendidikan Nusantara Global, 2025)
This study aims to analyze the embodiment of early childhood character values in the animated film Jumbo and investigate its relevance in character learning practices at the Pocenter Playgroup. The method applied is a qualitative approach through library research and content analysis, in addition to limited field observations. Data were obtained through narrative analysis of segments in the film that include eighteen character values. The research findings show that the film Jumbo presents character values clearly and emotionally through characters, conversations, and conflicts related to the world of children. At the Pocenter Playgroup, this film is used as a learning tool through discussions, role-playing, and thematic activities that support the internalization of values in children. This study concludes that local animated films such as Jumbo can function as effective educational media for character education for preschool children if supported by contextual and reflective teaching strategies. These findings contribute to the development of learning media that contain values and the implementation of character education in early childhood education environments.